2018
DOI: 10.5897/jphe2017.0983
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of community knowledge, attitude and practice on milk borne zoonoses disease in Debre- Birhan town, north Shewa, Ethiopia

Abstract: A cross-sectional questionnaire survey was conducted in Debre-Birhan town, North shoa, Ethiopia, with the objectives of assessing the knowledge, attitude and practices (KAP) of the study participants with respect to milk borne zoonoses; and to determine the effect of demographic character of respondents on knowledge, attitude and practice of zoonotic diseases. Data were collected from the respondents through administering semi-structured questionnaire across the randomly selected collection centers, retailers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 13 publications
1
11
2
Order By: Relevance
“…Men too, have a greater role in treating sick livestock and thus have access to insights on livestock diseases which could explain why they are more likely to have better knowledge on brucellosis. These findings correspond to other studies which have shown a variable effect of age, gender and formal education on knowledge of brucellosis [44][45][46][47]. Here it was also found that adherence to culture was a stronger driver for engaging in behavior risking transmission, than formal education.…”
Section: Culturally Acceptable Behavior Risking Transmission Of Brucellosissupporting
confidence: 91%
“…Men too, have a greater role in treating sick livestock and thus have access to insights on livestock diseases which could explain why they are more likely to have better knowledge on brucellosis. These findings correspond to other studies which have shown a variable effect of age, gender and formal education on knowledge of brucellosis [44][45][46][47]. Here it was also found that adherence to culture was a stronger driver for engaging in behavior risking transmission, than formal education.…”
Section: Culturally Acceptable Behavior Risking Transmission Of Brucellosissupporting
confidence: 91%
“…The level of knowledge on hygiene among milk vending machine handlers in this study was relatively low at a mean percentage of 68.83. In comparison with similar studies (Mandefero & Yeshibelay, 2018), milk handlers had poor scores on overall food safety knowledge, personal hygiene, and temperature control. This is attributed to a lack of adequate training on milk hygiene knowledge among handlers.…”
Section: Hygiene Knowledge Of Milk Handlerscontrasting
confidence: 63%
“…The results suggest that the use of narrative messages can promote healthy behaviour even when cultural norms are contrary to best health practices (Caudell et al ., 2019). In low income and/or developing countries there is a strong association between educational level and the knowledge of the population on milk borne zoonosis (Mandefero and Yeshibelay, 2018). These regions face challenges to increase the educational level of the whole population, and consequently reduce the incidence of diseases assocaited with raw milk consumption (Kumar et al ., 2017).…”
Section: Reducing the Risks Associated With Raw Milk In Food Servicesmentioning
confidence: 99%